Innovative Principles for Managing the Use of Mobile Software Tools - Ilhom Isxokovich Juraev (Research Parks Publishers, 2024)
Mobile software tools (MSTs) are increasingly significant in modern life, influencing various sectors such as education, business, healthcare, and entertainment. Effective management of MSTs is crucial for maximizing their benefits while mitigating potential risks. The insurance industry, in particular, has been transformed by the rapid adoption of digital technologies, allowing companies to deliver services through mobile applications and online platforms. Despite the growing trend of online insurance sales, disparities in accessibility and the efficiency of policy acquisition remain prevalent due to the absence of mobile applications in some cases. This chapter delves into strategies for integrating corporate applications, with a focus on architectural methodologies, integration approaches, and systems available for streamlining insurance policy sales.